Self-repairing asphalt material and preparation method thereof
By combining microcapsule technology with self-repairable agents to form self-repaired asphalt materials, the problems of untimely maintenance and high cost of asphalt pavement in the prior art are solved, and automatic repair and durability of road surfaces are achieved.
Patent Information
- Application Number
- CN202411845487.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-02-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, asphalt pavement maintenance and repair rely on regular manual intervention, with problems of untimely and high cost, and traditional methods cannot fundamentally improve the overall performance and durability of the road.
Microcapsule technology is used to combine self-repairing agents with asphalt materials to form self-repairing asphalt materials. When cracks or wear occur on the asphalt road surface, the microcapsules will automatically break, and release self-repairing agents for filling and repair, realizing self-repairing of the road surface.
It realizes automatic repair of road surfaces, reduces maintenance costs and workload, improves road usage efficiency and safety, extends the service life of the road, and maintains a stable repair effect under different climates and road conditions.
Smart Images

Figure CN119410169A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of road construction materials, and in particular, to a self-repairing asphalt material and a preparation method thereof. Background Art
[0002] In today's society, road construction and maintenance are important components of urban development and transportation system operation. With the continuous acceleration of urbanization, people's requirements for road quality and safety are getting higher and higher. However, due to temperature changes, excessive vehicle load, water damage, aging and other problems, asphalt pavement cracks, wear and tear, etc., seriously affecting the service life and safety of the road.
[0003] At present, the maintenance and repair of asphalt pavement mainly rely on regular maintenance work, such as filling cracks and re-paving asphalt. The traditional maintenance method has the following problems: First, the maintenance cycle is long, and a large amount of manpower, material and financial resources need to be invested regularly; if maintenance is not carried out in time, the cracks will increase. Secondly, the maintenance process has a certain degree of interference with road traffic, causing inconvenience and safety hazards to drivers and pedestrians. In addition, traditional maintenance methods can often only solve local problems on the road surface, and cannot fundamentally improve the overall performance and durability of the road. Therefore, there are problems of untimely and high cost for regular maintenance by personnel. Summary of the invention
[0004] The purpose of the present invention is to provide a self-repairing asphalt material and a preparation method thereof in view of the above-mentioned deficiencies in the prior art, so as to solve the problems of untimely and high cost of regular maintenance by personnel in the prior art.
[0005] This application combines microcapsule technology with a self-repairing agent to form an asphalt material with self-repairing function. Microcapsules are tiny capsule structures with a size ranging from a few microns to hundreds of microns, and are filled with self-repairing agents. When tiny cracks or wear appear on the asphalt pavement, the microcapsules will automatically break and release self-repairing agents to fill the cracks, thereby achieving self-repair of the road surface. The microcapsules of this application can automatically repair cracks without human intervention, greatly reducing the cost and workload of road maintenance. Secondly, the repair process will not interfere with road traffic, improving the efficiency and safety of road use. In addition, the material has good durability and stability, and can play a stable repair effect under different climate and road conditions. The material of this application can automatically repair when there is minor damage on the road surface, thereby extending the service life of the road, reducing maintenance costs, and improving the safety and comfort of the road.
[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows: The present application provides a self-repairing asphalt material, including asphalt and microcapsules mixed in the asphalt, the doping amount of the microcapsules is 1-10wt%, the microcapsules include a capsule body and a filler, the filler is a self-repairing agent, and the material of the capsule body is urea-formaldehyde resin.
[0007] Furthermore, the self-healing agent includes a polymer repairing agent, an active filler, and an activator.
[0008] Furthermore, the polymer repair agent is cyclopentadiene, and the active filler is iron oxide or calcium silicate.
[0009] Furthermore, the size of the microcapsules is 50-200 μm.
[0010] The present application also provides a method for preparing a self-repairing asphalt material, the method comprising the following steps: S1, preparation of microcapsules; S2, mixing the microcapsules with asphalt.
[0011] Furthermore, step S1 includes the following steps: S11, synthesis of urea-formaldehyde resin precursor; S12, Synthesis of microcapsules.
[0012] Furthermore, step S11 includes: dissolving urea in deionized water, adding formaldehyde solution, adjusting the pH value to 8.0-9.0, reacting at 70° C. for 1 hour, and cooling to room temperature to obtain urea-formaldehyde resin prepolymer.
[0013] Furthermore, step S12 includes mixing sodium dodecylbenzene sulfonate, molten dicyclopentadiene, and deionized water at 400 rpm for 30 minutes to obtain a dicyclopentadiene emulsion, adding urea-formaldehyde resin prepolymer, ammonium chloride, and resorcinol to the dicyclopentadiene emulsion, adjusting the pH value to 3.0, acidifying for 30 minutes, and then reacting at 60°C for 3 hours to obtain microcapsules.
[0014] Furthermore, step S2 includes the following steps: heating the mixture of asphalt and petroleum ether to soften it, adding a stabilizer, and then adding microcapsules and mixing them evenly; performing an aging treatment, and finally heating to remove the petroleum ether to obtain a self-repairing asphalt material.
[0015] Furthermore, the heating temperature of the mixture of asphalt and petroleum ether is 50° C. and the heating time is 1 h.
[0016] Compared with the prior art, the beneficial effects of the present invention are as follows: the present application fills the microcapsules with a self-healing agent and mixes with asphalt. When cracks occur, the microcapsules rupture and release the self-healing agent inside to repair the cracks; timely repair of small cracks avoids the occurrence of large cracks, and the repair effect is better. It has a good repair effect on both surface and internal micro cracks. It solves the problems of untimely and high cost of regular maintenance by personnel, and brings a new solution to road construction and maintenance. The present invention not only improves the durability and safety of roads, but also reduces maintenance costs, and has broad application prospects and economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The SEM characterization result of the microcapsules obtained in step S12 of the method for preparing a self-repairing asphalt material provided by the present invention; Figure 2 The SEM characterization results of the asphalt material obtained by the preparation method of the self-repairing asphalt material provided by the present invention; Figure 3 This is an image of the self-repairing asphalt material of the present invention before repair; Figure 4 This is the image after repair by the self-repairing asphalt material of the present invention. DETAILED DESCRIPTION
[0018] In order to make the implementation process of the present invention clearer, it will be described in detail below with reference to the accompanying drawings.
[0019] The present application provides a self-repairing asphalt material, including asphalt and microcapsules mixed in the asphalt, the doping amount of the microcapsules is 1-10wt%, preferably, the doping amount of the microcapsules is 5wt%, and the doping amount of 5wt% can ensure that when cracks occur, the number of microcapsules is sufficient to cover the crack area, thereby effectively releasing the self-repairing agent for filling and repair. Below 5wt%, the number of microcapsules may be insufficient, the amount of repair in the crack is insufficient, and a good repair effect cannot be achieved; when the doping amount is higher than 5wt%, too many microcapsules will cause the toughness and strength of the asphalt to decrease, and the increase in the amount of microcapsules will change the internal distribution of the asphalt and weaken the strength of its continuous phase, especially under load pressure, which will cause the risk of asphalt cracking or damage to increase, which is not conducive to the bearing capacity and durability of the road, and will also cause the rheology to decrease, affecting the paving and construction performance. The microcapsule includes a capsule and a filler, the filler is a self-repairing agent, and the self-repairing agent includes a polymer repair agent, an active filler, and an activator, which is used to initiate the self-polymerization of the filler to achieve the purpose of repairing asphalt. The polymer repair agent has excellent bonding properties, effectively filling cracks and bonding damaged areas together to restore the integrity of asphalt. The introduction of polymers improves the elasticity of the material, making it less likely to crack under temperature changes and loads. The active filler reacts chemically with the polymer repair agent to form a stronger cross-linking network, enhancing the mechanical properties of the asphalt material and improving the compressive and tensile strength. The activator can accelerate the cross-linking reaction of the polymer repair agent, improve the performance of the material during the curing process, and ensure a rapid response when cracks appear. The polymer repair agent undergoes a cross-linking reaction with the functional components in the active filler, enhancing the interaction between the polymer chains, thereby improving the mechanical strength and durability of the material.
[0020] The polymer repair agent is cyclopentadiene, the active filler is iron oxide or calcium silicate, and the activator is ferrocene. The mass ratio of polymer repair agent, active filler, and activator is 100:5:1, in order to achieve the highest degree of polymerization, ensuring the fluidity, adhesion, and curing speed of the material during the repair process. The material of the capsule is urea-formaldehyde resin; the amino and hydroxyl functional groups in the urea-formaldehyde resin react chemically with the active groups in the asphalt to form stable covalent bonds or hydrogen bonds, which enhance the adhesion between the microcapsules and the asphalt matrix to achieve better bonding with the asphalt. When the asphalt cracks and the cracks extend to the capsule, the capsule breaks and releases the repair agent. The repair agent fills the cracks and undergoes self-polymerization to repair the asphalt; urea-formaldehyde resin has good compatibility, ensuring the uniform distribution of microcapsules in the asphalt, thereby improving the overall performance of the material; in addition, urea-formaldehyde resin has good resistance to acid, alkali and other solvents. During the use of asphalt, urea-formaldehyde resin can maintain good stability and is not easily affected by the external environment. The size of the microcapsule is 50-200μm; if it is too small, the filler load is too small, and if it is too large, it is easy to break. Such a size can achieve a more ideal release rate, which is neither too fast to cause waste of active ingredients, nor too slow to affect the repair effect.
[0021] The present application also provides a method for preparing a self-repairing asphalt material, the method comprising the following steps: S1, preparation of microcapsules. Specifically comprising the following steps: S11, synthesis of urea-formaldehyde resin precursor. Urea was dissolved in deionized water, and then formaldehyde solution was added. The concentration of formaldehyde solution was 65 wt% to ensure that the synthesis reaction of urea-formaldehyde resin was fully carried out, which promoted the cross-linking reaction of urea-formaldehyde resin, formed high molecular weight polymer, and enhanced the performance of resin. The pH value was adjusted to 8.0-9.0 by dripping sodium carbonate solution. If the pH value was too low, it would cause resin degradation or unnecessary side reactions; if it was too high, it would affect the stability of the polymer. The reaction was carried out at 70°C for 1h. If the time was too long, it would cause over-polymerization or degradation; if the time was too short, it might be insufficiently synthesized. At a temperature of 70°C, the molecular movement was accelerated, which significantly increased the reaction rate and accelerated the synthesis of urea-formaldehyde resin, which could avoid the degradation of resin caused by excessive temperature and ensure the effective progress of the reaction. If the temperature was too low or the time was too short, the polymerization degree of the precursor would be low, and the obtained capsule could not fully wrap the filler and could not form microcapsules. The urea-formaldehyde resin prepolymer was obtained by cooling to room temperature. The urea-formaldehyde resin prepared in this way has good adhesion, can form a good interaction with the asphalt material, enhance the repair effect, and ensure the integrity of the repair area. The mass ratio of urea to formaldehyde is 1:2.3 to ensure that the content of dimethylol urea in the prepolymer is sufficient, which can enhance the net structure of the urea-formaldehyde resin product; specifically, a polycondensation reaction occurs between urea and formaldehyde to form a cross-linked structure of urea groups and formaldehyde. Under the above ratio, the content of dimethylol urea is sufficient, which has excellent cross-linking ability, enhances the cross-linking network of the resin, and improves its mechanical strength and heat resistance.
[0022] S12, synthesis of microcapsules. Sodium dodecylbenzene sulfonate (SDBS), molten dicyclopentadiene (DCPD), and deionized water were mixed at 400 rpm for 30 min to obtain a dicyclopentadiene emulsion. The amount of SDBS used was about 5% of the mass of DCPD, so that the dispersibility and stability of the emulsion were good. Urea-formaldehyde resin prepolymer, ammonium chloride, and resorcinol were added to the dicyclopentadiene emulsion. Ammonium chloride was a urea-formaldehyde resin curing agent, which played a role in curing the urea-formaldehyde resin to form capsules. Resorcinol was a urea-formaldehyde resin waterproof modifier, which played a role in promoting the formation of spheres. The mass ratio of urea-formaldehyde resin prepolymer to DCPD was about 2:1 to ensure the encapsulation effect of the microcapsules. If the ratio was too large, the encapsulated microcapsules had less fillers and could not achieve the best repair effect. If the ratio was too small, the fillers could not be fully utilized, which increased the cost. The dosage of ammonium chloride and resorcinol is approximately 1.5% and 2.5% of the prepolymer mass, respectively, to ensure the curing and modification effect of the wall material. Too low a ratio will increase the brittleness of the capsule and cause rupture during the mixing process with asphalt, and the modified asphalt will lose its self-healing effect.
[0023] Subsequently, acetic acid was added to adjust the pH value to 3.0, which would induce polymerization of the prepolymer and form a capsule structure. Acidification was performed for 30 minutes to obtain a complete spherical microcapsule. The acidification time affected the capsule thickness. A long acidification time resulted in a thick capsule, which was difficult to break after being stressed, reducing the repair effect. A short acidification time resulted in a thin capsule, which resulted in the risk of breaking the microcapsule when mixed with asphalt. The microcapsules were then reacted at 60°C for 3 hours to obtain microcapsules with a moderate capsule thickness and a size of 100 microns. The SEM characterization results are shown in Figure 1. Figure 1 shown.
[0024] S2, mixing the microcapsules with asphalt.
[0025] Heat the mixture of asphalt and petroleum ether at a mass ratio of 1:0.5, the optimal ratio for dissolving asphalt to ensure full dissolution without wasting materials. The heating temperature of the mixture of asphalt and petroleum ether is 50°C and the heating time is 1h to soften it. Then add a stabilizer, which is 0.2 wt% of resorcinol, to prevent the asphalt from condensing. Low concentrations can easily cause the asphalt to condense prematurely, affecting the uniform mixing of microcapsules and asphalt and reducing the repair effect. Then, add the microcapsules obtained in step S1 at a mass fraction of 5 wt%, and continue stirring for 2h to fully mix. Perform aging treatment at 60 o C for 4 h; finally, o C for 1 h to remove petroleum ether, and obtain a self-repairing asphalt material. The asphalt in the present application can be any asphalt material. In the embodiment, it is BS16 asphalt. The SEM characterization of the asphalt material doped with microcapsules is as follows: Figure 2 As shown, the spherical structure shown in the yellow box is the microcapsule. The microcapsules are evenly distributed in the asphalt, ensuring that cracks in any position of the asphalt will cause the microcapsules to break and release the repair agent, thus achieving the purpose of repairing the asphalt.
[0026] Electric shock is used to form cracks inside the asphalt to detect the repair effect. After the electric shock, cracks are formed inside the asphalt. Figure 3 This is the image before repair; the cracks extend to the microcapsules, causing the capsules to rupture and release their contents; after 15 minutes, the cracks inside the asphalt are repaired to a certain extent. Figure 4 This is the restored image. Figure 4 The cracks at the corresponding positions are filled to achieve repair. The application material has a strong ability to quickly repair asphalt cracks, and achieves rapid self-repair of asphalt cracks.
[0027] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A self-repairing asphalt material, characterized in that: The material includes asphalt and microcapsules mixed in the asphalt, the doping amount of the microcapsules is 1-10wt%, the microcapsules include a capsule body and a filler, the filler is a self-healing agent, and the material of the capsule body is urea-formaldehyde resin.
2. The self-repairing asphalt material according to claim 1, characterized in that: The self-healing agent comprises a polymer repairing agent, an active filler and an activator.
3. The self-repairing asphalt material according to claim 2, characterized in that: The polymer repair agent is cyclopentadiene, and the active filler is iron oxide or calcium silicate.
4. The self-repairing asphalt material according to claim 3, characterized in that: The size of the microcapsules is 50-200 μm.
5. A method for preparing a self-repairing asphalt material, characterized in that: The method comprises the following steps: S1, preparation of microcapsules; S2, mixing the microcapsules with asphalt.
6. The method for preparing the self-repairing asphalt material according to claim 5, characterized in that: The step S1 comprises the following steps: S11, synthesis of urea-formaldehyde resin precursor; S12, synthesis of the microcapsules.
7. The method for preparing the self-repairing asphalt material according to claim 6, characterized in that: The step S11 comprises: dissolving urea in deionized water, adding formaldehyde solution, adjusting the pH value to 8.0-9.0, reacting at 70° C. for 1 hour, and cooling to room temperature to obtain urea-formaldehyde resin prepolymer.
8. The method for preparing the self-repairing asphalt material according to claim 7, characterized in that: The step S12 comprises mixing sodium dodecylbenzene sulfonate, molten dicyclopentadiene and deionized water at 400 rpm for 30 minutes to obtain a dicyclopentadiene emulsion, adding urea-formaldehyde resin prepolymer, ammonium chloride and resorcinol to the dicyclopentadiene emulsion, adjusting the pH value to 3.0, acidifying for 30 minutes, and then reacting at 60° C. for 3 hours to obtain the microcapsules.
9. The method for preparing the self-repairing asphalt material according to claim 8, characterized in that: The step S2 comprises the following steps: heating the mixture of the asphalt and petroleum ether to soften it, adding a stabilizer, and then adding the microcapsules and mixing them evenly; performing an aging treatment, and finally heating to remove the petroleum ether to obtain a self-repairing asphalt material.
10. The method for preparing the self-repairing asphalt material according to claim 9, characterized in that: The heating temperature of the mixture of the asphalt and the petroleum ether is 50° C., and the heating time is 1 hour.
Citation Information
Patent Citations
Polymer group composite material self-repairing nano-scale capsule and preparation method thereof
CN101269311A
Urea resin wrapped dicyclopentadiene nanometer microcapsule, and synthetic method and application thereof
CN102492174A
Asphalt material with self-repairing function and preparation method thereof
CN106832969A
Microcapsule modified asphalt with enhanced self-healing characteristic and preparation method
CN115232483A
Self-healing asphalt containing microcapsules
KR1020160000995A
Cited By
A comb polymer asphalt modifier, a high-efficiency self-healing modified asphalt based thereon and a preparation method thereof
CN122790188A